2018
DOI: 10.15744/2393-9060.5.207
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Infertility and Nutrition

Abstract: The problem of infertility could arise from the woman, the man or both of them and sometimes it could stem from without a reason. The reasons of male infertility could be varicocele, idiopathic infertility, obstruction, undescended testis, immunological mechanisms, ejaculation disorder, testicular insufficiency, medicine-radiation effect, endocrine disorders such as diabetes, excessive consumption of alcohol, smoking and environmental toxins such as pesticides and lead. It is also believed that societies, obes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…Seminal parameters viz. semen volume, sperm concentration and sperm motility varies with age (Maya et al, 2009), climatic conditions (Miyamoto, 2012), regions (Adiga et al, 2008), dietary habits (Sanlier et al, 2018), environment, lifestyle (Blay et al, 2020), nature of occupation (Tayawade & More, 2018), mobile usage (Agarwal et al, 2011), type of clothes wearing (Parazzini et al, 1995;Mínguez-Alarcón et al, 2018), sleep pattern (Jhuang et al, 2021). In conclusion, in spite of some variations in the seminal parameters of oligoasthenozoospermic and normozoospermic males, the fertilization capacity of sperm in terms of fertilization rates of the semen of these males was similar during ICSI.…”
Section: Discussionmentioning
confidence: 99%
“…Seminal parameters viz. semen volume, sperm concentration and sperm motility varies with age (Maya et al, 2009), climatic conditions (Miyamoto, 2012), regions (Adiga et al, 2008), dietary habits (Sanlier et al, 2018), environment, lifestyle (Blay et al, 2020), nature of occupation (Tayawade & More, 2018), mobile usage (Agarwal et al, 2011), type of clothes wearing (Parazzini et al, 1995;Mínguez-Alarcón et al, 2018), sleep pattern (Jhuang et al, 2021). In conclusion, in spite of some variations in the seminal parameters of oligoasthenozoospermic and normozoospermic males, the fertilization capacity of sperm in terms of fertilization rates of the semen of these males was similar during ICSI.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that vitamin C supplement has a positive impact upon stress-induced infertility due to its testosterone-increasing and antioxidant effects. It is also stated that high-dose of vitamin C supplementation increases the testosterone level by affecting the hypothalamus–pituitary–testis axis ( 73 ) . Antioxidants thought to be associated with infertility are vitamins A, C, E, zinc, selenium, glutathione, coenzyme Q10, carnitine and lycopene.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, obesity causes changes in gonadotropin release (GnRH), which is a decrease in sex hormone-binding glonulin (SHBG). Growth hormones and growth factor proteins such as insulin, increased levels of leptin and decreased levels of adinopectin (Sanlier and Yorusun, 2018).…”
Section: Univariate Analysismentioning
confidence: 99%